ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, INVESTASI DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN KONOMI KOTA PAREPARE - Suhardi, Dayu (Universitas Muhammadiyah Parepare, 2018)
This study analyzes Regional Original Income , Funds of Balance, Investment and Government Expenditure Funds are independent variables in this study. This study aims to determine the effect of Regional Original Revenue, Balancing Funds, Government Investment and Spending on the Economic Growth of Parepare City. The economic growth data used is the constant value of Gross Regional Domestic Product. Secondary data on the variables of Economic Growth and independent variable data were taken from the Central Statistics Agency of the City of Parepare for the period 2007-2016. This research uses quantitative descriptive analysis method with multiple regression analysis approach. The results showed that partially the Regional Original Revenue, Balancing Fund variables had a positive but insignificant effect. Whereas Government Investment and Expenditures are partially negative but not significant to Economic Growth. Furthermore, simultaneously Regional Original Revenue, Fund balance, Investment and Government Expenditures have no significant effect on Economic Growth.